Replenishment cost of a storage system modelled through a defective renewal equation - Ferreira, M. A. M. (Acta Scientiae et Intellectus, 2015)
A storage system where a k units stock is replaced instantaneously, when required, is presented in this work. It is also supposed a Poisson demand. It is proved that the storage system replenishment cost expected present value function fulfills a defective renewal equation, being proposed for it an asymptotic expression.